Odpowiedzialność za wychowanie dzieci w wybranej literaturze wczesnochrześcijańskiej - Szczur, Piotr (Vox Patrum, 2013)
This article is a presentation of the problem of parents’ responsibility in raising their children. The first part shows a few general, but fundamental aspects of child upbringing in the Greco-Roman world. The next part describes ancient Christian texts written in Syria about the given problem (Didascalia Apostolorum, Constitutiones Apostolorum and selected works by St. John Chrysostom). These texts contain sincere admonishments to bring up children in accord with Christian ideals. Parents were sensitized to see the need for well-rounded moral and religious education of their children as well as for guarding them from negative influence of the surrounding world. The ultimate goal of such education was the salvation of the child (and the parents). In order to achieve this aim parents were required to use severe methods such as physical punishment, and to become more involved as educators, teachers and people responsible for the Christian formation of their children. It appears from these texts that although ancient Christian thinkers drew extensively from the achievements of classical culture in the field of child education and tried to transplant worthy ideals on the Christian ground, yet they gave them a different dimension and directed them toward a different aim.